Hepatoprotective and Renoprotective effect of Moringa oleifera Seed Oil on Dichlorvos-induced Toxicity in Male Wistar rats (Nigerian Journal of Physiological Sciences, 2022)
The liver and the kidney are one of the vital organs of body. Drug-induced toxicity is one of the most common problems encountered by these organs. The search for an effective medicine to treat this toxicity without any side effects has led to the use of traditional-based medicine. This study evaluated the effect of ethanolic extract of Moringa oleifera seed oil on hepatic and renal markers in dimethyl 2, 2-dichlorovinyl phosphate (DDVP, known as dichlorvos)-exposed Wistar rats. Twenty-one male Wistar rats were randomly divided into three groups of seven animals each. Group A served as the negative control and were not exposed to dichlorvos. Group B served as the positive control and were exposed to dichlorvos for 2 minutes but received no extract. Group C animals were exposed to the dichlorvos and received 300mg/kg of extract (Moringa oleifera seed oil) for 7days before and 21days after exposure. Exposure to DDVP led to a significant increase in hepatic & renal markers, inflammatory markers, decrease in plasma protein and alteration of plasma electrolyte. Moringa oleifera seed oil regulated and significantly enhanced plasma protein, reduced elevated levels of hepatic & renal markers, inflammatory markers in the study sample. In addition, histopathology observation showed that Moringa seed oil was able to regenerate the hepatorenal damage on exposure to dichlorvos. Conclusion: Moringa oleifera seed oil exhibited hepato-protective, nephroprotective properties and could be explored in nutrition and health.